Ethane groups modified DNA nanopores to prolong the dwell time on live cell membranes for transmembrane transport - Li, Yuan; Chen, Xiaolei; Lv, Cheng; Cheng, Yu (Frontiers in Chemistry, 2023)
Transmembrane transport, mostly relying on biological channels, is crucial for the metabolic process of live cells including sensing, signaling, cellular communicating and molecular transport. Artificial biomimetic channels offer excellent opportunities for studying the mechanisms of the metabolic process of live cells and promote the applications of gene transfection, drug delivery, and regulations of cellular communications. DNA nanopores can be designed flexibly and operated easily while maintaining good biocompatibility, offering a good candidate for applications in basic research. However, because of the small size and good biocompatibility of DNA nanopores, it is still difficult to form stable channels on the plasma membrane of live cells by DNA nanopores. As a result, it significantly limits the application of DNA nanopores in vivo. Thus, in this work, we have constructed ethane-phosphorothioate (PPT) groups modified DNA nanopores (E-DNA nanopores) to stimulate biological channels for the transmembrane transport of small molecules. The E-DNA nanopores were found to be more hydrophobic and stable to anchor at the plasma membrane of live cells for a longer time window for subsequent transmembrane transport after the modification of ethane-PPT groups. The membrane-spanning E-DNA nanopores with a longer dwell time window could inspire the design of new DNA nanostructures and expand their biological applications including biosensing and sequencing, construction of artificial cells and regulation of transmembrane transport.